Curcumin attenuates liver injury by modulating the AGE–RAGE axis and metabolic homeostasis in high-fat diet/streptozotocin-induced type 2 diabetic mice - Li, Mengyao; Zhang, Chunmei; Ma, Junyu; Zeng, Bangzhao; Li, Xuexun; Zhao, Xin; Bi, Xiaoyan; Li, Rong; Gao, Qin; Jiang, Yang; Ya, Fuli (Frontiers in Nutrition, 2025)
BackgroundDiabetic liver injury is a serious complication of type 2 diabetes mellitus (T2DM). Curcumin (CUR), a natural polyphenol derived from Curcuma longa, exhibits diverse biological activities. This study investigated the hepatoprotective effect of CUR against liver injury in a high-fat diet/streptozotocin (HFD/STZ)-induced T2DM mouse model and elucidated the underlying mechanisms.MethodsWe integrated network pharmacology to identify common targets between CUR and T2DM, followed by molecular docking to evaluate binding affinities to key targets. In vivo, T2DM mice induced by HFD/STZ were administered dietary CUR (800 mg/kg diet) for 4 weeks. Hepatic oxidative stress, inflammatory markers, key signaling pathways, and metabolomic profiles were analysed.ResultsNetwork pharmacology revealed 256 overlapping targets between CUR and T2DM. Protein–protein interaction (PPI) analysis identified AKT1, TNF, TP53, IL-6, and EGFR as central hub targets. KEGG pathway enrichment suggested the involvement of the advanced glycation end products (AGE)–RAGE signaling pathway in the protective effects of CUR. Molecular docking demonstrated strong binding affinities of CUR with RAGE, AKT1, and TP53. In vivo, CUR supplementation significantly improved hyperglycemia and reduced hepatic oxidative stress and inflammation in T2DM mice. CUR inhibited the AGE–RAGE pathway and modulated downstream PI3K/Akt and NF-κB signaling. UPLC–MS/MS-based metabolomics analysis indicated that CUR altered metabolic pathways related to galactose, glycine/serine/threonine, propanoate, and nicotinate/nicotinamide.ConclusionCUR protects against diabetic liver injury by inhibiting AGE–RAGE-induced inflammation and metabolic dysregulation. The protective mechanism involves modulation of the AGE–RAGE axis and restoration of metabolic homeostasis.